Implementasi Manajemen Strategi Dalam Meningkatkan Kinerja perbankan Syariah - Aulya, Mimma Alif (Maliki Interdisciplinary Journal, 2025)
In carrying out internal activities in banking, there needs to be regulation in improving effective and efficient organizational performance. One of them is by implementing strategic management to achieve the banking goals themselves, namely improving effective and efficient organizational performance. Developments in the current global economy have resulted in competition between banks in controlling and maintaining the market in the global economy. Banks compete with each other in their business competition. With the increase in the number of customers and economic growth, this makes Islamic banking compete with other Islamic banks in order to become the main one in providing trust and satisfaction to customers. Strategic management is needed to determine what strategy is in accordance with the steps to be taken. Therefore, strategic management is needed so that in every policy that is set there are no mistakes. Because every mistake in policy making will have a negative impact on the bank, either losses in the form of reduced income, or loss of customers. To improve the performance of Islamic banking, a SWOT analysis needs to be carried out to determine what strengths and weaknesses exist in the internal banking, as well as what opportunities and threats will occur externally in the banking.